EVIDENCE OF WITNESSES AS A MEANS OF PROVIDING IN THE ECONOMIC PROCESS - Козирєва, Валентина Петрівна; Хомченко, Олена Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article is devoted to the analysis of the new institute of economic procedural law of Ukraine - the testimony of a witness as a means of proof. Research methods: analyzed the approaches of various scientists about the feasibility of introducing a legal institute of witnesses, the norms of the current national legislation governing the use of such a means of evidence as evidence and foreign experience. Result: identifying ways to improve the regulatory consolidation of the testimony of witnesses in the Economic Procedural Code of Ukraine. Discussion: problems of domestic legislation and practice related to the legal status of a witness arising from the resolution of economic disputes. The outdated procedural legislation of Ukraine has been in need of reformation and significant changes for a long time. In order to unify and simplify the procedural aspects of legal proceedings, a number of existing procedural norms have been changed, and the legislative base has been supplemented with new views, including, among other things, commercial procedural law, the expediency of which should be analyzed. Among such novels, there is a new institute of witnesses in the commercial procedural law. With the advent of the witness as a new full-fledged procedural participant in commercial courts, procedural law was supplemented by a new means of proof - testimony of the witness. Among the lawyers there is a widespread perception that the greatest threat to such reforms is the prospect of the loss of operationality in dealing with cases, as it is in civil proceedings because of the abuse of witnesses at a court session. The legislator has minimized the possibility of abuse, by establishing a number of significant restrictions both on the identity of the witness and on his testimony. Firstly, witness’s testimony, which cannot contains the sources of his knowledge in certain circumstances, or words based on the messages of others can`t be an evidence. Secondly, the establishment of facts is substantially narrowed based on testimony. Changes to economic procedural legislation have become a progressive step towards improving the judicial process in resolving business disputes and opening up more opportunities in implementing the principle of competition in commercial legal proceedings. An interesting novel in the economic process is the regulation of the possibility of a written poll of participants in the case as witnesses. Despite the positive changes in procedural legislation, such a novels cannot be considered perfect, as claimed by domestic lawyers. The procedural legislation of Ukraine truly becomes closer to the legal standards of Europe, since most states use testimony as a means of proof in the commercial process. Analyzing the novels of the Code, it should be emphasized that the domestic legislator has borrowed many procedural rules of international law. For example, in American law system there is the statement «Hearsay rule» that means the prohibition of providing evidence of circumstances that the witness did not perceive directly, but known to him from other people’s words. Quite similar to the statement of the witness is the notion of «affidavit» from the American law system. The affidavit in this sense can be considered as a written testimony (statement of the fact), given under the oath.